Laser-bonding in high power electronics - Schmidt, Michael; Weigl, Markus (Journal of Laser Micro Nanoengineering, 2010)
In the field of high power electronics a trend towards higher thermal loadings, a rising power density and also the need for enhanced dynamic strengths can be seen. These requirements make great demands on the joining technologies, which is why soldering and brazing processes are cumulatively replaced by welding applications. By means of welding it is possible to achieve connections based on metal-joints, featuring a high operating temperature and an excellent electric conductivity. In order to realize short processing times with a concentrated energy input and a high degree of automation, laser systems are well-adapted to meet these challenges. The present article deals with methods and possibilities to increase the mechani-cal and electrical characteristics of laser-welded copper-aluminum connections. Upon other terms, the influence of a lateral laser-beam displacement towards the aluminum base material and the effects of a pulse modulation within a single laser pulse are discussed. For example, a lateral beam displacement leads to a shifting of the maximum thermal contraction at the end of the laser pulse into the aluminum. Due to the lower yield strength and the higher ductility of pure aluminum in con-trast to pure copper, the maximum residual stresses can be reduced by plastic deformation.
Created from Fastlane, Scopus look-up
Keywords: Aluminum; Bonding; Copper; Ductility; Laser